Xylan recovery from dilute nitric acid pretreated oil palm frond bagasse using fractional factorial design - Nurul Aishah, Mazlan; Kamaliah, Abdul Samad; Wan Mohd Hafizuddin, Wan Yussof; Rozaimi, Abu Samah; Jamaliah, Md Jahim (Malaysian Palm Oil Board, 2021)
Pretreatment enhances bioconversion of lignocellulosic biomass by disrupting and changing the properties of its material. This work is intended to examine the influence of several variables involved in the recovery of xylan from oil palm frond bagasse (OPFB) in the pretreatment of diluted nitric acid. Through a fractional factorial design of 25−1 the temperature variables ranged from 37°C–90°C, time of reaction varied from 6–24 hr, solid loading ranged from 5%–20%, concentration of acid changed from 0.01%–1.0%, and agitation between yes or no were evaluated. As much as 27.63% of xylan successfully recovered at mild condition and it was completely hydrolysed as the pretreatment condition increased. This study found solid loading of 5% and acid concentration of 0.01% at 37°C for 24 hr pretreatment without agitation were best to maximise xylan recovery and minimise lignin content simultaneously. Temperature was the most important factor studied for the recovery of xylan with a contribution of 29.34%. The findings suggest that studying the condition influencing acid pretreatment is crucial towards improving pretreatment process